Game Edukasi Ilmu Tajwid berbasis Android menggunakan Metode ADDIE untuk Meningkatkan Minat Belajar Siswa - Akhyanto Akhyanto; Nana Suarna; Ade Irma Purnamasari (Jurnal Informatika Terpadu, 2022)
The rapid development of technology, especially mobile phones, has a considerable impact, including in the school education environment. Children at the Madrasah Ibtidaiyah level are particularly vulnerable to the influence of these technological advances. The Quran is a guide for Muslims in various parts of the world. The way to read the Quran can be learned in tajweed learning. The learning process of tajweed at the Madrasah Ibtidaiyah level currently uses textbooks, explains the material, gives examples, and gives practice questions to students, which seem monotonous and make children bored to participate in learning activities. This study aims to develop an interactive and new-looking learning media to increase students' interest in learning tajweed. This study used the Research and Development version of the ADDIE model with five stages: Analysis, Design, Development, Implementation, and Evaluation. The ADDIE method has a systematic structure and steps that are simple and easy to learn. This research resulted in a learning media in the form of a tajweed educational game with the results of the respondent's achievement level test of 81.3% with a suitable category so that the game application can be used in Madrasah Ibtidaiyah.